Development of a highly specific assay for rapid identification of pathogenic strains of Yersinia enterocolitica based on PCR amplification of the Yersinia heat-stable enterotoxin gene (yst). - Ibrahim, A (1997)
The chromosomal gene yst, which encodes a heat-stable enterotoxin of Yersinia enterocolitica, is a useful diagnostic marker because it occurs only in invasive strains of this species. A homologous gene also occurs in some strains of Yersinia kristensenii. Sequence analysis of the yst genes from two different strains of Y. enterocolitica and from Y. kristensenii revealed a substantial number of mismatches at the 3' ends of the yst genes of the so-called American and European biotypes of Y. enterocolitica. Moreover, several mismatches and a deletion of 5 codons were found in the yst of Y. kristensenii. These findings were used to develop a PCR-based assay for yst of Y. enterocolitica which yielded a detectable product in as little as 50 min. The assay was 100% specific in terms of its ability to identify potentially pathogenic strains of Y. enterocolitica regardless of biotype or serotype. The PCR yielded an amplicon that was visible on agarose gel electrophoresis from as few as 100 CFU, or 10 CFU when the PCR was combined with dot blot hybridization with a digoxigenin-labeled oligonucleotide probe that corresponded to an internal sequence of yst. These results establish the value of the yst gene as a target for the identification of pathogenic bioserotypes of Y. enterocolitica and the usefulness of PCR for this purpose.